Studies on vegetative and reproductive growth of cucumber under insect proof net house - KUMAR, MUKUL; SIROHI, H S; SINGH, BALRAJ; TOMAR, B S; SINGH, AWANI KUMAR; SABIR, NAVED; DWIVEDI, P K (The Indian Journal of Agricultural Sciences, 2021)
A study was carried out at CPCT, IARI, New Delhi during kharif 2013-14 to evaluate the vegetative growth and insect-pest incidence on cucumber under insect proof net house. Significantly higher vine length (94.94 and 178.67 respectively) and number of leaf nod (17.74 and 26.45 respectively) at 30 and 45 days after transplanting, were recorded in seed parent and pollen parent under insect proof net house in comparison to open field. Time taken to opening of first female and male flower in seed parent and pollen parent (39.0 and 34.90 respectively) was significantly lower under insect proof net house. Production of female and male flowers (36.57 and 25.42) was significantly higher under insect proof net house compared to open field crop. Fruit set and matured fruit (5.71 and 2.52) per plant was significantly higher under insect proof net house than open field (2.84 and 1.65 respectively). Incidence of cucumber mosaic virus was negligible under insect proof net house (0%) as compared to open field conditions (56.86%). Therefore, it can be concluded that for growing virus free seed crop and attaining better fruit growth, flowering, fruit setting and mature fruit per plant, hybrid seed production of cucumber should be undertaken in insect proof net house.